Postacute administration of the GABAA α5 antagonist S44819 promotes recovery of peripheral limb fine motor skills after permanent distal middle cerebral artery occlusion in rats. Issue 2 (4th November 2020) - Pace, Marta; Falappa, Matteo; Machado, Patricia; Facchin, Laura; Hermann, Dirk M; Bassetti, Claudio L
Background: Ischemic stroke causes hypoexcitability in the peri-infarct motor neocortex that stems from increased tonic γ-amino-butyric acid (GABA) activity in neurons. This hypoexcitability, while neuroprotective in the acute phase, may impair neuroplasticity and functional recovery in the subacute phase of stroke. The purpose of this study is to investigate the effect of delayed and prolonged administration of S44819, which is a potent and competitive selective antagonist of GABAA receptors, on the skilled reaching function in a rodent model of stroke. Methods: Male Sprague–Dawley rats ( n = 15) were subjected to permanent middle cerebral artery occlusion. Starting 3 days after stroke, a vehicle or S44819 (3 or 10 mg/kg, BID) was delivered orally twice a day for 28 days. All animals were euthanized 2 weeks later after the washout period. A single pellet reaching task (SPR) was performed before (baseline value) and after the ischemic surgery at several time points (3, 10, 17, 24, 31, 38, and 45 days) to assess the motor deficit. Infarct volume and body changes were also evaluated. Results: S44819, administered at 10 but not 3 mg/kg, significantly improves SPR results over the 45 days after the ischemic surgery. No effect was observed in the infarct size and in the body weight over time between the groups investigated. Conclusion: S44819 at 10 mg/kg significantly enhances motor recovery on a skilled reaching task after sensory-motor cortex lesion. Additionally, our study, in light of the results of the RESTORE BRAIN (Randomized Efficacy and Safety Trial of Oral GABAA α5 antagonist S44819 after Recent ischemic Event) trial, may help clinicians to design clinical studies and stratify variables and patients adequately.